Double Integral Inequalities of Hermite-Hadamard-Type for ɸh-Convex Functions on Linear Spaces - Fagbemigun, B.O.; Mogbademu, A.A.; Olaleru, J.O. (Journal of Nepal Mathematical Society, 2019)
The concept of Φh-convexity is extended for functions defined on closed Φh-convex subsets of linear spaces. Consequently, some double integral inequalities of Hermite-Hadamard type defined on time-scaled linear spaces are established for Φh-convex functions.